Flexible labour policies as competitive advantage - Antunes, F.; Pereira, L.; Dias, Á.; Vinhas da Silva, R. (Global Journal of Flexible Systems Management, 2023)
The emergence of the Covid-19 pandemic and the constant changes in the expectations and needs of employees have accelerated the implementation of labour flexibility policies by companies. Currently, there is some uncertainty in the literature about the real benefits of adopting these policies, hence the relevance of this research, which aims to assess whether they represent a source of sustainable competitive advantage. This research used a qualitative approach involving in-depth interviews with human resource managers to analyse the impact of labour flexibility policies on a firm's competitive advantage using the VRIO framework. The study found that while employees view labour flexibility as beneficial to their work-life balance and job satisfaction, from the perspective of firms, these policies may be valuable but do not provide a distinct competitive advantage. Consequently, companies need to consider these policies when developing strategies to maintain their competitiveness and market position.